A new dynamic word learning task to diagnose language disorder in French-speaking monolingual and bilingual children - Matrat, Mélodie; Delage, Hélène; Kehoe, Margaret (Frontiers in Rehabilitation Sciences, 2023)
Tools to effectively assess the language performance of bilingual children are lacking. Static tests assessing vocabulary knowledge (e.g., naming task) are not appropriate for testing bilingual children due to different types of bias. Alternative methods have been developed to diagnose bilingual children, including measuring language learning (e.g., word learning) through dynamic assessment. Research conducted with English-speaking children indicates that DA of word learning is effective in diagnosing language disorders in bilingual children. In this study, we examine whether a dynamic word learning task, using shared-storybook reading, can differentiate French-speaking (monolingual and bilingual) children with developmental language disorder (DLD) from those with typical development (TD). Sixty children (4–8 years), 43 with TD and 17 with DLD, participated: 30 were monolinguals and 25 were bilinguals. The dynamic word-learning task used a shared-storybook reading context. The children had to learn four non-words, paired with novel objects, as well as their semantic characteristics (a category and a definition) during the reading of a story. Post-tests assessed the recall of the phonological form and the semantic features of the objects. Phonological and semantic prompts were given if the child was unable to name or describe the objects. Results indicated that children with DLD performed less well than those with TD on phonological recall, leading to fair sensitivity and good specificity at delayed post-test for young children (4–6 years). Semantic production did not differentiate the two groups: all children performed well at this task. In sum, children with DLD have more difficulties encoding the phonological form of the word. Our findings suggest that a dynamic word learning task using shared-storybook reading is a promising approach for diagnosing lexical difficulties in young French-speaking, monolingual and bilingual, children.